Cymbopogon citratus biochar as a fertilizing and remediating agent for soils with high copper content - Vanessa Susana Rech Bisi; Wendel Paulo Silvestre; Marcos Henrique Tramontin; Elaine Damiani Conte; Marcelo Godinho; Gabriel Fernandes Pauletti (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The use of biochar and its products has been increasing in recent years. However, although being studied, most of the potential of biochar to be used as a remediating and fertilizing agent is still unclear. Given this, the present work aimed to assess the effect of different concentrations of Cymbopogon citratus (lemongrass) biomass applied to soil contaminated with Cu.